Pelatihan Ekonomi Syariah: Migrasi Koperasi Konvensional Menjadi Koperasi Syariah dan Pendirian Koperasi Syariah - Nanang Sobarna (E-Coops-Day, 2023)
Changes in cooperatives from conventional systems to cooperatives based on Sharia principles are important in cooperative business activities because they have an impact on the principles and use of contracts in collecting and distributing financing to members. Systematic education improvement regarding the migration of conventional cooperatives to sharia cooperatives in the form of training is an effort to bind understanding for supervisors, administrators, and managers of the Bandung Branch of Bank BTN Retired Cooperative who have the desire to migrate from conventional cooperatives to cooperatives based on sharia principles. The purposChanges in cooperatives from conventional systems to cooperatives based on Sharia principles are important in cooperative business activities because they have an impact on the principles and use of contracts in collecting and distributing financing to members. Systematic education improvement regarding the migration of conventional cooperatives to sharia cooperatives in the form of training is an effort to bind understanding for supervisors, administrators, and managers of the Bandung Branch of Bank BTN Retired Cooperative who have the desire to migrate from conventional cooperatives to cooperatives based on sharia principles. The purpose of this training is to get to know and increase understanding for supervisors, administrators, and managers of the Bandung Branch of the Cooperative of Purnakarya Bank BTN regarding the migration of conventional cooperatives to sharia cooperatives. The method used in this training is the lecture method which is assisted by visually displaying the material so that the training material can be easily understood. Then proceed with questions and answers and discussion accompanied by problem-solving solutions. Through this training, supervisors, administrators, and managers have been able to understand the process and stages of migrating conventional cooperatives to Sharia cooperatives, including that the migration process must be based on the approval of the Member Meeting, there is a transition process, amendments to the Articles of Association are made, must apply sharia principles, there are changes business activities, and conventional cooperatives that have become sharia cooperatives cannot return to conventional cooperativese of this training is to get to know and increase understanding for supervisors, administrators, and managers of the Bandung Branch of the Cooperative of Purnakarya Bank BTN regarding the migration of conventional cooperatives to sharia cooperatives. The method used in this training is the lecture method which is assisted by visually displaying the material so that the training material can be easily understood. Then proceed with questions and answers and discussion accompanied by problem-solving solutions. Through this training, supervisors, administrators, and managers have been able to understand the process and stages of migrating conventional cooperatives to Sharia cooperatives, including that the migration process must be based on the approval of the Member Meeting, there is a transition process, amendments to the Articles of Association are made, must apply sharia principles, there are changes business activities, and conventional cooperatives that have become sharia cooperatives cannot return to conventional cooperatives